Comparison of historical and current temperatures in show caves (Slovenia) - Stanka Šebela (Springer, 2021)
Abstract Historical air temperatures at three karst caves in Slovenia have been compared to current data time series. In Postojnska Jama (PJ), the most visited show cave in Slovenia, the significant temperature difference between historical and modern measurements at the Pulpito site relates to the months April to November. Mean monthly temperatures measured at the Sepolcro site (PJ) in the modern period (2016–2019) are year round significantly higher than in the historical period (1935–1937). The temperature increase over the last 85 years in PJ is attributed to outside temperature rise and additional heat input from visitors, especially for Sepolcro site. A comparison of current (2017–2019) and historical (1956–1957) temperature data in touristically poorly visited Predjama Cave shows lower increase as in PJ and is completely related to outside cave conditions. In the case of Škocjanske Jame (Tiha Jama), air temperature has not significantly increased since the historical 1928 measurements because the monitoring site looks to be morphologically isolated from significant impacts of outside climate and visitors.